Viral diversity and phloem transcriptional changes in grapevine Shiraz disease infected vines - Cristobal Onetto; Dilrukshi Nagahatenna; Yeniu Mickey Wang; Vinay Pagay; Anthony Borneman (OENO One)
Shiraz disease (SD) is a highly destructive disease of grapevines that is associated with grapevine virus A (GVA) infection of vineyards in Australia and South Africa. However, little is known about the transcriptional modifications in grapevine phloem tissues induced by SD. In this study, we explored the viral diversity and transcriptional changes linked to SD. Vines symptomatic for SD exhibited higher viral abundance and were also shown to be co-infected with both GVA and grapevine leafroll-associated virus (GLRaV-4) strain 9. Differential gene (DE) expression analysis revealed physiological responses of Vitis vinifera to the infection. Similar to other plant pathogen infections, SD upregulated genes associated with the systemic acquired resistance (SAR) mechanism and downregulated genes related to vine immunity. Additionally, upregulated genes suggests that callose deposition and the blocking of phloem sieve elements are likely employed by V. vinifera as a defence strategy to limit the internal spread of SD viruses.